Anti-Cancer Effect of Phosphatidylcholine Containing Conjugated Linoleic Acid at sn-2 Position on MCF-7 Breast Cancer Cell Line - Riska Rian Fauziah; Chin Rie; Tomoyuki Yoshino; Shinjiro Ogita; Yukihiro Yamamoto (Universitas Pendidikan Indonesia, 2022)
Conjugated linoleic acid (CLA) exhibits anti-cancer effects; however, most studies have only investigated its free fatty acid forms (CLA-FFA). Here, we compared the anticancer effect of CLA with its lipid forms (FFA and phosphatidylcholine [PC]) on the breast cancer cell line MCF-7 with Soy-PC as a control. CLA-FFA, CLA-PC, and Soy-PC caused a dose- and time-dependent inhibition of MCF-7 growth. However, the lowest antiproliferative activity was observed with CLA-PC. These results were consistent with Hoechst staining and protein expression of apoptosis markers Bax and Bcl-2. Interestingly, CLA-PC uptake was four times lower than that of Soy-PC, which may have affected its antiproliferative effect. Many papers showing that phospholipid forms of functional compounds have superior activity than intact forms have been reported, however, our results suggest that the PC form of CLA was inferior to its FFA form in inhibiting MCF-7 cell growth. This is the first report showing that the phospholipid form is not always the superior form.